Changes in the satisfaction with consulting services according to the opinion of entrepreneurs in North-Eastern Hungary 2001-2016 - Ágnes Tokár-Szadai (Journal of Contemporary Economic and Business Issues, 2017)
The Institute of Business Sciences of the University of Miskolc carried out a survey of management consulting firms and enterprises in 2001, 2005-2006 (Szadai, 2007), 2011-2012 (Tokár-Szadai, 2014), and 2015-16 in North-eastern Hungary. The goal of our surveys was to determine the status (importance) of business consulting in our region (North-eastern Hungary) and examine the changes in the entrepreneurs' experiences with consulting services over the last 15 years.The satisfaction with consultants and the results of consulting services have improved a little, but haven't changed significantly in the last 15 years. According to our surveys, more solutionoriented proposals would make the consultants more convenient to their clients.
Keywords: L84; M53; O15; 330; survey; satisfaction; management consulting service; client; northeastern Hungary